PEACE AND HARMONY IN THE WORLD BASED ON PANCASILA AND BHINNEKA TUNGGAL IKA (Unity in Diversity) - Diane Butler (Harmoni, 2016)
Indonesia, the largest archipelago with over 17,500 islands, is the fourth most populated country and one of the most culturally and linguistically diverse nations composed of about 500 ethnic groups using 746 vernacular languages. For centuries an influx of peoples from South-East Asia, Indochina, India, Arabia, Polynesia, Europe, and the Americas has augmented its multiculturality. Yet, a majority of the peoples still live in fruitful coexistence. Thus, this paper seeks to show that the ideology of Pancasila (Five Principles) and Bhinneka Tunggal Ika (Unity in Diversity) is a valuable basis for interculture in cultural environments, peace and harmony not only for Indonesia but for the whole of humanity in the world. To do so, it will reflect on writings stemming from the work of former Secretary-General of the United Nations and President of the World Commission on Culture and Development Javier Pérez de Cuéllar on fostering a culture of peace and “Our Creative Diversity”.